Legal Protection of Medical Waste Management in Community Health Centers : An Environmental Sustainability Analysis. - Arry Suarthawan, Made; Jayantari, I Gusti Agung Mas Rwa; Utami, Putu Ayu Sani; Arjawa, I Gst Pt Bagus Suka (Dinasti Research, 2025)
This study aims to analyze the regulation of medical waste management in Community Health Centers and its impact on environmental displacement. This study uses a normative legal method with a regulatory approach (statutory approach), contextual (conceptual approach), and analysis (analytical approach). Data sources include regulations, scientific journals, and related literature. The results of the study indicate that although national regulations such as Law Number 18 of 2008 and Minister of Health Regulation Number 7 of 2019 have been implemented, their implementation still encounters obstacles. Factors such as lack of waste management infrastructure, minimal understanding of medical personnel, and weak supervision cause medical waste management to be suboptimal. The impacts include soil, air, and air pollution, as well as the risk of spreading diseases that endanger public health and the environment. Thus, it is necessary to strengthen regulations, improve facilities, and provide effective supervision and training to support environmental demand